Experimental study of the moisture content influence on CH adsorption and deformation characteristics of cylindrical bituminous coal core - Dingyi Hao; Lei Zhang; Mingxue Li; Shihao Tu; Cun Zhang; Qingsheng Bai; Chen Wang (Adsorption Science & Technology)
Moisture content in coal is an important factor affecting the coal seam gas extraction. It directly affects the storage and flow of gas in bituminous coal. In this paper, the cylindrical bituminous coal cores of Xutuan coal mine in Huaibei coal mine group were studied as experimental objects, using the laboratory self-designed experimental device Gas Adsorption and Strain Testing Apparatus system . The influence of the bituminous coal moisture content on gas adsorption characteristics was studied. Drying experiments of coal samples showed that they lose the original moisture content following the exponential decay function of time. At wetting, the saturated moisture content in coal samples increased following the Exponential Association function of time. The experimental results show that the average original moisture content and average saturated moisture content of raw coal samples are 1.3 and 2.4%, respectively. On this basis, the gas adsorption experiments on samples with different moisture contents under different gas pressures were carried out. With the moisture content increase, the gas adsorption capacity and saturation value decreased and the decrease rate gradually reduced. The single exponential decay function describes the gas adsorption capacity dependence on moisture content. Moisture content also affects the adsorption deformation of bituminous coal. At high moisture content, the adsorption deformation of bituminous coal is less.